Mechanical Properties of Composites Reinforced with Recycled Paper and Pine Needles Using Polymer Matrices Containing 50 to 70% Dammar Resin - Cosmin Mihai Miritoiu; Adrian Sorin Roșca; Dragoș Tutunea (BioResources)
The main objective of this study was to manufacture and test environmentally friendly composite materials using biomass residues as reinforcement: pine needles and recovered paper. A mixed matrix was also used, with natural dammar resin as the predominant component, in order to favor the eco-friendly nature of the resulting material. The manufacturing process employed was the lay-up hand technique. Another objective was to investigate how dammar resin influences the mechanical properties as its mass percentage increases in the mixed resin composition. To investigate the influence of dammar resin on the mechanical properties of the composites, additional materials were fabricated for comparison, using the same reinforcements but with two types of synthetic matrices: epoxy and acrylic. The samples were tested for tensile strength, compression, bending, Shore D hardness, and vibrations.The results indicated that as the percentage of dammar in the matrix increased, a decrease in the strength and rigidity of the material occurred, accompanied by an increase in elasticity and ductility. Water absorption tests showed that the saturation process occurred much faster, as pine needles tend not to absorb a significant amount of water due to the presence of lignin, wax, resins, and pectin, which act as a natural water-repellent barrier.